Long covid syndrome experienced by children in West Sumatra, Indonesia - Basra, Mega Utami; Djafri, Defriman; Putri, Anggela Pradiva (Intelektual Pustaka Media Utama, 2023)
In several countries, it has been found that people experienced symptoms of COVID-19 even after several weeks or months since they were declared cured or tested negative. This symptom is known as the long COVID-19 syndrome. This study aimed to get an overview of the long COVID-19 syndrome experienced by children. This study was a cross-sectional study conducted in West Sumatra, Indonesia in August-October 2021. The sample was 214 children younger than 18 years old. The results showed that after more than four weeks tested positive for COVID-19, 28.5% of children still have respiratory disorders, 26.2% experienced symptoms of sleep disorders, 23.4% of children experienced fatigue, 11.2% of children experienced symptoms of memory disorders, and 8.42% experienced symptoms of digestive disorders. Although not as much as in adults, this study shows that long COVID-19 syndrome can also occur in children. The clinical manifestations of long COVID-19 were varied in symptoms and can occur alone or in combination simultaneously. Parents should continue to optimize their child's time to rest even though they have declared negative for COVID-19 and keep an eye on the symptoms that still appear.